BIPA (Indonesian for Foreign Speakers) as an Educational Tourism Program in Bali: Opportunities and Challanges - Suprastayasa, I Gusti Ngurah Agung; Ariasri, Nyoman Reni (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2023)
One form of tourism that has grown significantly around the world is educational tourism. The potential of Indonesian for Foreign Speakers (BIPA) as an educational tourism destination offering educational experiences is discussed in this study. The study's methodology is a qualitative one because the issues under investigation concern actors in the tourism and education industries' attitudes and perspectives on BIPA as one of Bali's main interests for international tourists. Data were collected by interviewing a number of key informants including the BIPA program director of the Balai Bahasa Bali, BIPA teachers, a faculty member who is also involved in an international program at Udayana University, a number of individuals involved in the tourism industry, including the current and previous president of the Indonesian Tour Guide Association, tourism observers, and academics. The study's findings indicate that BIPA has the potential to become one of Bali's top draws for visitors looking to learn the Balinese and Indonesian languages.